A phase I study of the CDK4/6 inhibitor ribociclib combined with gemcitabine in patients with advanced solid tumors - Aurora Norman; Mahesh Seetharam; Jacob Allred; Jianping Kong; Mateusz Opyrchal; Wen Wee Ma; Yanyan Lou; Grace K. Dy; Amit Mahipal; S. John Weroha; Andrea E. Wahner Hendrickson; Joel M. Reid; et al. (BJC Reports)
Abstract Background Based on preclinical data showing addition of CDK4/6 inhibitors to gemcitabine was synergistic, ribociclib was evaluated in combination with gemcitabine to determine the maximum tolerated dose (MTD) and dose limiting toxicities (DLT). Methods In this single arm multicohort phase I trial, we evaluated the safety and efficacy of ribociclib plus gemcitabine in patients with advanced solid tumors. Patients received gemcitabine intravenously on days 1 and 8 followed by ribociclib days 8–14, with treatment repeated every 3 weeks. Results The study enrolled 43 patients between October 2017 and September 2019. The escalation phase (19 patients) determined the MTD and recommended phase II dose (RP2D) to be ribociclib 800 mg daily and gemcitabine 1000 mg/m2 for the expansion phase (24 patients). One patient experienced Grade 4 thrombocytopenia. Eleven patients experienced Grade 3 adverse events (AE), the most common being neutropenia, thrombocytopenia, and anemia. No partial or complete responses were observed. 15/22 (68%) of efficacy evaluable patients who received the MTD achieved best response of stable disease. Conclusions The addition of ribociclib to gemcitabine was tolerated well and yielded stability of tumors in both cohorts. Biomarkers such as Rb status and activity of CDK2 and CDK4/6 complexes may help to select patients who may respond better to the combination of gemcitabine and ribociclib. Clinical Trial Registration NCT03237390.